The Effect of Snack Consumption on Body Mass Index and Body Fat Percentage in Students During the COVID-19 Pandemic - Clemarie Tholib; Prissilia Nanny Djaya (School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, 2023)
Introduction: Corona virus disease 2019 (COVID-19) is an infectious disease caused by SARS-CoV-2 and has been determined as a pandemic by the World Health Organization (WHO). As an effort to reduce transmission, the government has announced several policies that encourage working from home, which will increase snack time. This will have an impact on increased calorie intake and risk of obesity. Therefore, it is necessary to identify the effect in young adults that requires balanced nutrition. This study aims to understand whether snacks consumption has an effect on body mass index and body fat percentage in university students. Methods : A total of 76 pre-clinical students from Atma Jaya Catholic University of Indonesia participated in this cross-sectional study, which was conducted during the pandemic. The data was collected using anthropometric measurement, Snacks-Food Frequency Questionnaire, and body fat scale. Chi-square analysis was performed with Statistical Package for the Social Sciences (SPSS). Results : 52.9% of the subjects were female, 42.9% had normal body mass index, 48.6% had normal body fat percentage, 52.9% rarely eats healthy snacks, 51.4% often eats unhealthy snacks. According to statistical calculations, there are significant effects on unhealthy snacks consumption with body mass index (p=0.033) and body fat percentage (p=0.013). Conclusions : There are significant effects of snacks consumption on body mass index and body fat percentage in Atma Jaya Pre-clinical Students during COVID-19 pandemic. Keywords: Young Adult, COVID-19, Snacks Consumptions, Fat Mass, S-FFQ, Body Mass Index